2018
DOI: 10.1080/13658816.2018.1436713
|View full text |Cite
|
Sign up to set email alerts
|

How do cyclists make their way? - A GPS-based revealed preference study in Copenhagen

Abstract: It is the objective of the study to determine the extent to which human navigation is affected by perceptions of our immediate surroundings or by already established knowledge in terms of a cognitive map. The motivation is to contribute to the knowledge about human navigation and to inform planning with estimates of bicyclists' route preferences and 'willingness-to-pay' (in terms of transport distance vs utility/disutility of route characteristics). The core method is choice modelling of observed route data. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The difference in distance between actual and shortest routes in this study was greater than reported by others [40] [57] [58] [59], however was not statistically significant. Findings lend support to previous studies that have shown cyclists prefer to travel on lower stress roads, but also value directness [25] [40] [58] [60]. In our sample, cyclists may have chosen slightly longer routes in order to travel on lower stress roads, but were unwilling to travel the excessive distances required to travel on exclusively low stress routes, if available.…”
Section: Discussionsupporting
confidence: 87%
“…The difference in distance between actual and shortest routes in this study was greater than reported by others [40] [57] [58] [59], however was not statistically significant. Findings lend support to previous studies that have shown cyclists prefer to travel on lower stress roads, but also value directness [25] [40] [58] [60]. In our sample, cyclists may have chosen slightly longer routes in order to travel on lower stress roads, but were unwilling to travel the excessive distances required to travel on exclusively low stress routes, if available.…”
Section: Discussionsupporting
confidence: 87%
“…Studies about how to determine bicycle routes in cities emerge in various fields (e.g., urban geography, transportation, urban planning and urban design) and pay attention on the concerns about health and physical activity, healthy living, sustainable transportation and non-motorized transportation (e.g., Saelens et al 2003, Huang and Ye 1995, Wendel-Vos et al 2004, Segadilha and da Penha Sanches 2014, Blečić et al 2015. Deploying GIS tools, the researchers about bicycle network planning emphasize the route choice criteria for bicycling in relation to the physical, infrastructural and natural characteristics of settlements (e.g., Rybarczyk and Wu 2010) and to the modelling of bicyclists' route preferences by GPS records as well as to cycling demand of population in terms of transport distance and quality of route utilities (e.g, Skov-Petersen et al 2018).…”
Section: How To Determine Bicycle Routes?mentioning
confidence: 99%
“…Despite the fact that E3S Web of Conferences 164, 04007 (2020) TPACEE-2019 https://doi.org/10.1051/e3sconf /202016404007 every second resident of Copenhagen owns a car, over fifty percent of urban residents use bicycles to travel around the city. The share of residents that travel around the city by cars, has plummeted to 24% [12]. It is assumed that the cycling transport development produces impact on communications between residents of the Danish capital [13].…”
Section: Transportation System Patterns: the Global Experiencementioning
confidence: 99%